PENGARUH WISATA PANTAI OLUHUTA TERHADAP PENDAPATAN MASYARAKAT DI KABUPATEN BONE BOLANGO - Fitria Akibun; Kida, Riyanto M.; Mokodongan, Regi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to analyze the influence of Oluhuta Beach tourism on the income of the community in Oluhuta Village, Bone Bolango Regency. As a coastal area rich in natural and cultural potential, tourism development is expected to enhance local community welfare. This research employs a qualitative descriptive approach, with data collection techniques including interviews, observations, and documentation. Informants consist of officials from the Tourism and Creative Economy Office of Bone Bolango, village government, and local tourism managers. The results show that the government's role as a regulator has not been optimal due to the lack of government involvement, with tourism activities managed independently by the community. Conversely, the roles as a dynamizer and facilitator have been effective through training programs and promotional activities. However, as a catalyst, the government has not fully succeeded in accelerating coastal tourism development, partly due to community resistance against retribution policies. This study concludes that Oluhuta Beach tourism holds significant potential to increase community income, but achieving optimal success requires strengthening synergy between the government and the community through effective communication and inclusive policies.